Parental Strategies in Introducing English for young Learners - Amiruddin, Nurul Khairiyah; Saiful, Saiful; Qalbi, Nur (Universitas Cokroaminoto Palopo, 2025)
This study aims to see how the strategies used by parents in order to start and introduce English to their children who are young learners. English education is very important to be taught to young learners from an early age. Parents have an important responsibility towards their children's English education. Parents can start learning English for their children from an early age by applying various learning strategies. This research was conducted qualitatively by using research instruments in the form of interviews with 7 parents as a method of data collection. This study categorizes several strategies used by parents in the context of teaching their children English. The results showed that parents introduced their children to English in various ways, such as introducing vocabulary, using a vocabulary memorization system, using fun learning methods, and using learning media.